BILDUNGSROMAN FOR CHARACTER EDUCATION IN HIGHER EDUCATION: AN INDONESIAN CONTEXT - Novianti, Nita (International Journal of Education, 2017)
Considering the lack of research on character education in higher education, this paper proposes that Bildungsroman, a genre concerned with a protagonist’s development and education from childhood to adulthood, fits perfectly into the recent need of literary works for teaching character education in college. Employing literature review, this paper argues that Bildungsroman satisfies the major requirements for literary works for character education in college drawn from O’Sullivan (2004). Bildungsroman also provides a rich source for cultivation of character traits as stipulated by the Indonesian Department of National Education (2010). Furthermore, the general theme of self-development is highly appropriate to the nature of character education in higher education, namely as a continuation and consolidation of the character developed in college students’ previous education. It is expected that the present study will contribute to the teaching of character education through literature, although further studies are required in order to explore the effective teaching and learning techniques.